(untitled) (Research, Society and Development, 2020)
Introduction: Diabetes mellitus type 1 (DM1) is considered an autoimmune, chronic, multifactorial disease, which involves the progressive destruction of β cells in pancreatic islets, which are responsible for the production of insulin, thus resulting in the loss of production and secretion of same. It is estimated that more than 30 thousand Brazilians suffer from this pathology. Three mechanisms are responsible for the destruction of these cells: genetic susceptibility, autoimmunity and environmental factors. In this sense, the objective of this study was to carry out a survey about the main perspectives of cure of this disease using the CRISPR / Cas9 system. Methodology: This is a bibliographic review with searches in national and international electronic databases in Portuguese and English. Results: Since this pathology still has no cure, only treatment, the CRISPR / Cas9 system emerges as a promising therapy, as well as therapy with pluripotent menenchymal stem cells (MSC), which have the functionality, mainly, of repair and survival of β cells from pancreatic islets, MSCs have the ability to modify the microenvironment of the areas of pancreatic injury, canceling the autoimmune destruction against β cells and can restore the patient’s normoglycemia. Conclusion: Bearing in mind that this is a pathology of a genetic nature, CRISPR / Cas9 associated with therapy with pluripotent mensenchymal cells has been shown to be a versatile and effective tool in the treatment of DM1. However, there is a need for further research capable of inducing strategies for the improvement of genetic alterations and greater efficiency of the therapeutic effect.